2016
DOI: 10.5032/jae.2016.02075
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Student Teacher Critical Thinking through Blogs in an Electronic Community of Practice

Abstract: Technology is becoming increasingly popular in higher education

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…To manage the limited water resources and encourage water conservation, Extension and agricultural educators need to understand not only how people use water, but also the cognitive and behavioral aspects of water conservation (Gorham, Lamm, & Rumble, 2014;Gregory & Di Leo, 2003;Lamm, Lamm & Carter, 2015;Leal, Rumble, & Lamm, 2015;Warner, Lamm, Rumble, Martin, & Cantrell, 2016). The most important group to target for the promotion of water conservation would be high water users, as they utilize most amount of water (Huang, Lamm, & Dukes, 2016;. Huang et al (2016) compared high water users with the general public and found that compared to general public, high water users were wealthier, had obtained a higher level of education, and lived in a homeowner's association (HOA).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To manage the limited water resources and encourage water conservation, Extension and agricultural educators need to understand not only how people use water, but also the cognitive and behavioral aspects of water conservation (Gorham, Lamm, & Rumble, 2014;Gregory & Di Leo, 2003;Lamm, Lamm & Carter, 2015;Leal, Rumble, & Lamm, 2015;Warner, Lamm, Rumble, Martin, & Cantrell, 2016). The most important group to target for the promotion of water conservation would be high water users, as they utilize most amount of water (Huang, Lamm, & Dukes, 2016;. Huang et al (2016) compared high water users with the general public and found that compared to general public, high water users were wealthier, had obtained a higher level of education, and lived in a homeowner's association (HOA).…”
Section: Introductionmentioning
confidence: 99%
“…The most important group to target for the promotion of water conservation would be high water users, as they utilize most amount of water (Huang, Lamm, & Dukes, 2016;. Huang et al (2016) compared high water users with the general public and found that compared to general public, high water users were wealthier, had obtained a higher level of education, and lived in a homeowner's association (HOA). High water users were also found to less likely to practice water conservation and other related social behaviors compared to the general public (Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher-level thinking skills have often been reported as important for an individual's education, as well as an important engagement technique for teachers (Whittington & Bowman, 1994: Torres & Cano, 1995Geertson, 2003;Christopher, Thomas, & Tallent-Runnels, 2004;Ulmer & Torres, 2007;Clark & Paulsen, 2016;Ganapathy, Singh, Kaur, & Kit, 2017). While researching the cognitive discourse of professors, researchers found that although professors wanted to teach at all cognitive levels, their discourse tended to be in the lower levels of cognition (Whittington, 1995;Ewing & Whittington, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The role of Extension educators is to provide the public with knowledge based on research, so the public will make informed decisions on local and national issues. Water conservation is one of the pinnacle issues that must be addressed by Extension educators (Lamm, Lamm, & Carter, 2015;Huang & Lamm, 2015a;Huang & Lamm, 2015b;Huang, Lamm & Dukes, 2016). Increases in agricultural production, irrigation, recreation, industry, and power generation have been leading to increased water scarcity as the population continues to grow (Adams et al, 2013;Hoekstra, Mekonnen, Chapagain, Mathews, & Richter, 2012, Huang et al, 2016.…”
Section: Introductionmentioning
confidence: 99%